Likelihood Methods for Nonstationary Time Series and Random Fields (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In this article we discuss a generalization of the Whittle likelihood approximation from stationary processes to locally stationary processes and random fields.